A CROSS-SECTIONAL STUDY OF OBSERVATION OF SERUM IRON AND LIVER FUNCTION TEST IN CHOLELITHIASIS, BIHAR, INDIA. - Vaidehi; Kumari, Kanchan; Kumar, Akhilesh; Prasad, Indu; Sahay, Yogesh Krishna (Student's Journal of Health Research Africa, 2023)
Objectives: Cholelithiasis, the formation of gallstones within the gallbladder, is a common gastrointestinal disorder. This study aimed to investigate the biochemical changes in cholelithiasis and identify the appropriate diagnosis that would aid the treatment plan for cholelithiasis. Materials and Methods: A cross-sectional study was conducted on 150 participants, including 75 patients diagnosed with cholelithiasis and 75 age and gender-matched healthy controls. Serum iron, ferritin and various liver enzymes e.g. SGPT,SGOT and ALPwere measured using a colorimetric method. Data obtained were analyzed using appropriate statistical tests. Results: The outcomes of this study discovered that people with cholelithiasis had lower values of serum iron (Mean ± SD: 60.74 ± 10.21 μg/dL) in comparison to the control group (mean ± SD: 78.29 ± 9.16 μg/dL) (p< 0.001). Additionally, the cholelithiasis group exhibited increased levels of liver function enzymes e.g. SGPT, SGOT, alkaline phosphatase, ferritin, bilirubin as comapred to that of the control group. Conclusion: Cholelithiasis is related to lower serum iron contents and changes in various other biochemical parameters which include higher levels of SGPT, SGOT, alkaline phosphatase(ALP), and bilirubin. These findings propose that cholelithiasis may additionally result in iron deficiency, which could be associated with chronic inflammation or other mechanisms. Further research is needed to discover the underlying mechanisms and medical implications of those observations in individuals with cholelithiasis.